Mental Disorder—The Need for an Accurate Definition - Telles-Correia, Diogo; Saraiva, Sérgio; Gonçalves, Jorge (Frontiers in Psychiatry, 2018)
There are several reasons why a definition for mental disorder is essential. Among these are not only reasons linked to psychiatry itself as a science (nosology, research), but also to ethical, legal and financial issues. The first formal definition of mental disorder resulted from a deep conceptual analysis led by Robert Spitzer. It emerged to address several challenges that psychiatry faced at the time, namely to serve as the starting point for an atheoretical and evidence-based classification of mental disorders, to justify the removal of homosexuality from classifications and to counter the arguments of anti-psychiatry. This definition has been updated, with some conceptual changes that make it depart from the main assumptions of Spitzer's original definition. In this article we intend to review the factors that substantiated the emergence of the first formal definition of mental disorder that based all its later versions.